Characterization, antioxidant, and antimicrobial activity of two sage species' organic and aqueous extracts from Morocco's Middle Atlas (Kuwait Journal of Science)
This study quantifies phenols and flavonoids and evaluates antioxidant and antibacterial activities in extracts of Salvia officinalis (SO) and Salvia blancoana subsp. mesatlantica (SB) from Immouzzer in the Middle Atlas, Morocco. Bioactive components from both plants were extracted, and their 2,2-diphenyl-1-picrylhydrazyl (DPPH), total antioxidant capacity (TAC), and ferric reducing antioxidant power (FRAP) were assessed in aqueous and organic extracts. Both extracts exhibited high levels of bioactive substances, antioxidant activity, and antibacterial properties. The highest total phenolic content (TPC) for SO and SB was in the methanol extract. SO's methanol extract had the highest total flavonoid content (TFC), while SB's aqueous extract showed the highest TFC. The methanol extract also demonstrated the highest DPPH antioxidant activity for both SB and SO, and the highest TAC levels were in the methanol extract of SB and the aqueous extract of SO. In SO, the methanol extract exhibited the highest FRAP, while SB's highest was in the ethanol extract. Both extracts demonstrated notable inhibition, with SB's ethyl acetate extract having the largest zone against Staphylococcus aureus, and SO's ethanol extract showing strong activity against Candida albicans. The ethanolic extract from SO had the lowest MIC and MBC values against Bacillus subtilis, and the lowest MIC values for Proteus mirabilis in SB were associated with the ethanolic and ethyl acetate extracts., while the lowest MBC values for both pathogens were with the ethanolic and dichloromethane extracts. Leaf extracts from both Salvia species may serve as natural antioxidants and antimicrobials for the food and pharmaceutical industries. © 2025 The Authors